Case study: A few letters on a corn stalk leaf led to a rapist and murderer - Busarčević, Miroslav; Simonović, Branislav (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article shows a case study of the rape and murder of an 18-year-old girl. The perpetrator sexually assaulted the victim in his car, which he parked in a cornfield, and then set her on fire. One of the most important pieces of evidence in that case was a reflection of damaged relief letters from the sidewall of a car tire, near the tread, pressed against a corn stalk leaf – the size of the imprint was 1 × 0.5 cm. The article describes the procedure of traceological expertise and concludes that analyzing the imprint in the discussed case was based on the same principles as the procedure of identifying a trace of an imprint made by a stamp on a piece of paper.
Keywords: traceological expertise; damaged relief letters of the car tire; reflection of letters on a corn stalk leaf